English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Solve simultaneously:
log(x-y-1)=0, log(xy)+1=0

2007-03-02 01:51:37 · 6 answers · asked by alexisvisjnic 1 in Science & Mathematics Mathematics

6 answers

10^log(x-y-1) = x-y-1 = 1

10^[(log(xy) + 1] = 10xy = 1

x-y-1 = 1
10xy = 1

y =x-2 into 10xy =1 and get

10x(x-2)=1
10x^2-20x-1 = 0


x1,2 = (20 +- sqrt(400 + 40))/20 = 1 +- sqrt(110)/10

x1 = 1 + sqrt(110)/10
y1 = sqrt(110)/10 - 1

x2 = 1 - sqrt(110)/10
y2 = -1 - sqrt(110)/10

Both are smaller than 0, so their product is positive which is in the log function's domain.

2007-03-02 02:20:35 · answer #1 · answered by Amit Y 5 · 1 0

log (x) = 0 is the same as x = 1. So, change the first one x - y - 1 = 1, or x - y = 2.

log(xy) = -1 is the same as xy = 1/10.

You are left with the (much simpler) equations:

x - y = 2
10xy = 1

Use the first to get y = x - 2. Plug this into the second to get:

10x(x-2) = 1

So, it looks like two solutions to me, the two solutions for

10x^2 - 20x - 1 = 0

Also, as Amit (next poster) points out, in one solution the x,y pair are both negative, yielding a positive product for the logarithm. Both solutions are therefore valid. You're right, this one is tricky!

2007-03-02 10:06:22 · answer #2 · answered by Anonymous · 0 0

log(x-y-1)=0 so x-y-1=10^0=1 and x-y=2 or x=2+y
log(xy)+1=0 so 10xy = 1
Thus 10(y+2)y = 1
y² +2y = 1/10
y = 0.0488 or -2.0488
so x = 2.0488 or 0.0488

2007-03-02 09:59:59 · answer #3 · answered by draco_mortifer 2 · 1 0

x=0, y=0

2007-03-02 10:01:02 · answer #4 · answered by rovelose1 2 · 0 2

I get x = 2+y = 2.0488088482. That makes y=the decimal part.

(I'm assuming base 10 logs.) You can ck:

log(2.0488088482-.0488088482-1) = ? and
log(2.0488088482 x .0488088482) + 1 = ?

(Answers wouldn't let me close my parentheses after the 1 in the next to last line.) BTW you have to discard any solutions that make the log argument negative, since logs of negatives are undefined.

2007-03-02 10:00:30 · answer #5 · answered by answerING 6 · 0 0

first equation-
x-y-1=e^0=1
x-y=2--------------(a)
2nd equation-
log(xy)=-1
xy=e^(-1)
xy=1/e--------------(b)
(x+y)^2=(x-y)^2+4xy
put values from equqtion (a)and(b)
(x+y)^2=4+4*(1/e)
now you will get value of (x+y)
then solve it with equation(a)
you will get answer.
Good Luck.
you can ask any type of maths problem personally,i'll feel glad to solve that because math is my passion.

2007-03-02 10:25:08 · answer #6 · answered by yogesh gulhania 2 · 0 0

fedest.com, questions and answers